Pengembangan Sistem Informasi Manajemen Proyek pada PT Solusi Integrasi Multikarya Menggunakan Metode SDLC Waterfall - Ruslan Wanandi; Herwis Gultom (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
PT Solusi Integrasi Multikarya requires an information system capable of managing projects effectively and in an integrated manner. Currently, project recording, scheduling, and reporting are still performed manually, leading to potential delays and administrative errors. This study aims to design and develop a web-based project management information system to improve efficiency and accuracy in project data management. The system is developed using the Software Development Life Cycle (SDLC) Waterfall model, which includes the stages of requirements analysis, system design, implementation, testing, and maintenance. The development uses PHP programming language, Laravel framework, and MySQL database. The expected result of this study is a project management information system that facilitates project management, monitors work progress, and generates real-time reports, thereby supporting performance improvement and decision-making within the company.